2017
DOI: 10.1016/j.jece.2017.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on mixed microbial culture polyhydroxyalkanoate production while treating a starch industry wastewater

Abstract: Influence of temperature on mixed microbial culture polyhydroxyalkanoate production while treating a starch industry wastewater, Journal of Environmental Chemical Engineeringhttp://dx.Engineering (Brisbane, Queensland, Australia); 4 Promiko AB (Lomma, Sweden).Corresponding author: Alan Werker (alan@werker.se) Graphical abstractHighlights  Enrichment biomass at 15 and 25 °C gave similar PHA accumulation potential  PHA accumulation process robust to temperatures from 15 to 30°C  Kinetics change with temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…For PHA production, a much All these factors can alter mass transport conditions for diffusion [15,23]. PHA accumulation and nitrogen conversion rates are also temperature dependent [24,25]. Present data were obtained at 22°C and sensitivity to temperature was not explored as part of this investigation.…”
Section: Resultsmentioning
confidence: 99%
“…For PHA production, a much All these factors can alter mass transport conditions for diffusion [15,23]. PHA accumulation and nitrogen conversion rates are also temperature dependent [24,25]. Present data were obtained at 22°C and sensitivity to temperature was not explored as part of this investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In anticipation of a scale‐up for the process of PHA accumulation, De Grazia et al. (2017) studied the influences of temperature on the conversion of activated sludge from potato starch wastewater with MMC and demonstrated that this parameter is not relevant for PHA productivity. Different results were reported by Setyawaty et al.…”
Section: Waste From Foods As a Carbon Source: Bioplasticsmentioning
confidence: 99%
“…SBR is typically operated through a succession of cycles, whose duration can be adapted according to the characteristics of the fermented feedstock (e.g., VFA concentration) [59,60]. Such cycles guarantee the occurrence of the feast period (C source availability) during the feed phase and part of the reaction phase (feast), whereas the culture faces starvation in the rest of the cycle (famine) [61].…”
Section: Role Of the "Feast And Famine Regime" In Mmc-pha Production ...mentioning
confidence: 99%
“…Such cycles guarantee the occurrence of the feast period (C source availability) during the feed phase and part of the reaction phase (feast), whereas the culture faces starvation in the rest of the cycle (famine) [61]. The ratio between the length of feast and the overall cycle length has been identified as the crucial parameter in establishing SBR is typically operated through a succession of cycles, whose duration can be adapted according to the characteristics of the fermented feedstock (e.g., VFA concentration) [59,60]. Such cycles guarantee the occurrence of the feast period (C source availability) during the feed phase and part of the reaction phase (feast), whereas the culture faces starvation in the rest of the cycle (famine) [61].…”
Section: Role Of the "Feast And Famine Regime" In Mmc-pha Production ...mentioning
confidence: 99%